Peran Musik Kontemporer dalam Pelestarian Budaya Tradisional di Ruteng, Manggarai, Flores, NTT - Avilla Desyani Jovina Bahang; Gede Budarsa; Putu Karina Pravitasari (Institut Nalanda, 2025)
This research discusses the role of contemporary music in preserving traditional culture in Ruteng, Manggarai, Flores, East Nusa Tenggara. Contemporary music is an effective medium in bridging traditional values ​​and modern expressions. Using a qualitative approach, this study explores the dynamics that occur in a number of art studios such as Wela Kaweng, Molas Balibelo, Terjang Wero, and Lulu Nai which actively create music and dance works based on local traditions but packaged in a contemporary style. The research results show that contemporary music not only maintains the existence of local musical instruments and motifs such as gong, gendang, kedendik and torok, but also plays a role in transmitting cultural values ​​through digital media and modern performances. Apart from that, contemporary music also encourages community strengthening, expands creative economic opportunities, and supports the development of tourism and cultural education. From a social perspective, this musical art strengthens solidarity between studio members and opens up space for cross-generational collaboration. From an economic perspective, studio activities contribute to MSMEs and income through performances and digital media monetization. In an educational context, studios become interactive learning spaces that instill cultural awareness in the younger generation. Contemporary music in Ruteng has proven capable of adapting to changing times without losing its local cultural roots, making it an inclusive, functional and sustainable cultural preservation strategy. This research recommends the need for continued support from the government and educational institutions to maintain the continuity of local creativity based on traditional wisdom.